Taking risks for personal gain: An investigation of self-construal and testosterone responses to competition. (2nd January 2019) - Welker, Keith M.; Roy, Ashlin R. K.; Geniole, Shawn; Kitayama, Shinobu; Carré, Justin M.
ABSTRACT: Recent research on testosterone and risk-taking behavior is beginning to focus on the role of context-dependent changes in testosterone. Extending this research, our study investigated the association between testosterone reactivity to competitive outcomes and risk-taking in the context of a video game based competition. The study also examined whether self-construal moderated this relationship. Results indicated that a rise in testosterone during competition did not predict subsequent risk-taking behavior. However, a rise in testosterone during competition predicted subsequent risk-taking behaviors within winners with independent self-construals. Nevertheless, results did not reveal an association between basal testosterone and risk-taking, nor did competitive outcomes modulate a differential testosterone response. Overall, we treat these findings as preliminary, as there were multiple analyses conducted and effect sizes were relatively small. We discuss these results in the context of recent animal findings that testosterone facilitates success at future competitions after winning a competition, as well as recent research suggesting self-construal moderates associations between testosterone and aggression.